Organically functionalized mesoporous SBA-15 as sorbents for removal of selected pharmaceuticals from water - Bui, Tung Xuan; Kang, Seo-Young; Lee, Sang-Hyup; Choi, Heechul (ELSEVIER SCIENCE BV, 2011)
Mesoporous silica SBA-15 and its postfunctionalized counterparts with hydroxymethyl (HM-SBA-15), aminopropyl (AP-SBA-15), and trimethylsilyl (TMS-SBA-15) were prepared and characterized by powder X-ray diffraction, N-2 adsorption-desorption measurement. Fourier-transform infrared spectroscopy, and elemental analysis. The removal of a mixture of 12 selected pharmaceuticals was investigated by batch adsorption experiments onto SBA-15 and the grafted materials. SBA-15 showed to have moderate adsorption affinity with amino-containing (atenolol, trimethoprim) and hydrophobic pharmaceuticals. but it displayed minimal adsorption affinity toward hydrophilic compounds. HM-SBA-15 was analogous with SBA-15 in terms of the adsorption efficiency toward all pharmaceuticals. AP-SBA-15 exhibited an increase in the adsorption of two acidic compounds (clofibric acid, diclofenac) but a decrease in the adsorption of estrone and the two amino-containing compounds. Among the grafted materials, TMS-SBA-15 had the highest adsorption affinity toward most pharmaceuticals. Moreover, the adsorption of nine pharmaceuticals to TMS-SBA-15 was significantly higher than that to SBA-15; seven of which showed the removal percentages from 70.6% to 98.9% onto TMS-SBA-15. The number of pharmaceuticals showing high adsorption efficiency onto TMS-SBA-15 did not alter significantly as the pH changed in the range of 5.5-7.6. The results suggest that TMS-SBA-15 is a promising material for the removal of pharmaceuticals from aqueous phase, especially for the treatment of wastewater from drug manufacturers. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: CONTAMINANTS; SURFACE; SILICA; ENVIRONMENT; ADSORBENTS